2022
DOI: 10.1007/978-3-031-16980-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of StyleGAN2-ADA on Medical Images

Abstract: Although generative adversarial networks (GANs) have shown promise in medical imaging, they have four main limitations that impede their utility: computational cost, data requirements, reliable evaluation measures, and training complexity. Our work investigates each of these obstacles in a novel application of StyleGAN2-ADA to high-resolution medical imaging datasets. Our dataset is comprised of liver-containing axial slices from non-contrast and contrast-enhanced computed tomography (CT) scans. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Thus, some studies argue that using FID for medical imaging is neither practical nor feasible and suggest replacing the inception network with their own encoding networks 46,47 . Nonetheless, recent studies using StyleGAN2 have reported their results using FID 21,45 , which is different from the approach of using their own encoding networks for FID evaluation in medical imaging. This is because the alternative approach lacks consistency in evaluating and comparing FID because it does not use the same encoding model as ImageNet 21,48 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, some studies argue that using FID for medical imaging is neither practical nor feasible and suggest replacing the inception network with their own encoding networks 46,47 . Nonetheless, recent studies using StyleGAN2 have reported their results using FID 21,45 , which is different from the approach of using their own encoding networks for FID evaluation in medical imaging. This is because the alternative approach lacks consistency in evaluating and comparing FID because it does not use the same encoding model as ImageNet 21,48 .…”
Section: Discussionmentioning
confidence: 93%
“…These results may appear unsatisfactory when compared with other medical studies. One study 21 reported FID scores of 5.22 (± 0.17) for a liver CT dataset on a StyleGAN2 network with transfer learning from the FFHQ dataset, and FIDs of 10.78, 3.52, 21.17, and 5.39 on the publicly available SLIVER07, ChestX-ray14, ACDC, and Medical Segmentation Decathlon (brain tumors) datasets. In another study 45 , the FID was approximately 20 for synthesized magnetic resonance and CT images.…”
Section: Discussionmentioning
confidence: 99%
“…The FID has been reported to be over-reliant on texture and is argued not to be directly transferable to medical images (Hong et al, 2021). Other works argue that FID aligns well with visual quality analyses (Woodland et al, 2022). In addition to FID, we therefore use the MedicalNet (Chen et al, 2019) for feature extraction before calculating the Fréchet Distance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above automated methods, evaluation approaches, which involve humans/experts, have also been used, for example, the visual turing test [ 41 ], five-point Likert scale [ 38 ], and human eye perceptual evaluation (HYPE) [ 39 ]. Although these methods are considered the most accurate methods and are the gold standard, they are costly and time-consuming.…”
Section: Related Workmentioning
confidence: 99%